Shrink-fitted joint behavior using three-dimensional solid finite elements in rotor dynamics with inclusion of stress-stiffening effect - Eerik Sikanen; Janne E Heikkinen; Jussi Sopanen (Advances in Mechanical Engineering, 2018)
In this article, the contact behavior of a shrink-fitted joint in a rotor assembly at different spin speeds is studied, using the three-dimensional solid finite element approach. A custom frictionless contact model is proposed and extensively tested by means of simulation. The theory for solving pre-stressed damped eigenvalue problem is presented and implemented, and the results are presented in Campbell diagram form. Two sample rotor assemblies are studied. In addition, experimental modal analysis results of a shrink-fitted joint with various interferences are presented and numerically studied. The reduction of the interference of the shrink-fitted joint due to centrifugal forces at high-speed operation as well as the contact status are updated at each rotational speed step. The inclusion of stress-stiffening effect is studied in detail. The comparison of the Campbell diagram results with the results obtained using a commercial finite element software (Ansys) shows a good agreement.